Some New Grüss’ Type Inequalities for Functions of Selfadjoint Operators in Hilbert Spaces - Dragomir, S. S. (Sarajevo Journal of Mathematics, 2024)
Some new inequalities of Grüss' type for functions of selfadjoint operators in Hilbert spaces, under suitable assumptions for the involved operators, are given. Several examples for particular functions of interest are provided as well. 2000 Mathematics Subject Classification. 47A63, 47A99